AD‐ASGKA – authenticated dynamic protocols for asymmetric group key agreement. Issue 11 (26th January 2016) - Li, Mingchu; Xu, Xiaodong; Guo, Cheng; Tan, Xing
Abstract: Asymmetric group key agreement is a cryptographic primitive allowing a group of users to negotiate a common public encryption key while each of them holds a different secret private decryption key. Anyone (including outsiders) with the public encryption key can send encrypted messages to the group members, and then the group members can decrypt the messages. Authenticated key agreement protocols authenticate the identities of users to ensure that only the intended group members can establish a session in which the group members can communicate with each other. Dynamic asymmetric group key agreement concerns about the scenarios such as ad hoc networks in which the group members may join or leave at any given time. In this paper, we propose a one‐round authenticated dynamic protocol for symmetric group key agreement. For efficiency reasons, we employ the identity‐based public‐key cryptography (IB‐PKC) to authenticate users rather than the public key infrastructure and the certificate‐less public‐key cryptography. Our analysis shows that the proposals in the paper can resist active attacks and meet many desirable security attributes. Besides, our protocol allows users to join or leave the group at the same time. Furthermore, our protocol is round‐optimal and has a quite good performance as compared with previous works. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper proposes a one‐round authenticated dynamic protocol for asymmetric group key agreement. The analysis shows that the proposals in this paper can resist active attacks and meet many desirable security attributes. Besides, our protocol allows users to join or leave the group at the same time. Furthermore, the protocol is round‐optimal and has a quite good performance as compared with previous works.